The Effects of Exenatide Once Weekly (EXQW) and Exenatide Twice a Day (EXBID) on Beta-Cell Function in Type 2 Diabetes: A Systematic Review and Network Meta-Analysis - Jie Wang; Xinye Jin; Ping An; Songyan Yu; Yiming Mu (Journal of Diabetes Research)
Background. In patients with type 2 diabetes mellitus (T2DM) and poor glycemic control receiving metformin (MET), glucagon-like peptide-1 receptor agonists (GLP-1 RAs) are recommended as the adjunctive therapy. However, there are only a few studies involving the comparative effects of exenatide twice a day (EXBID) and exenatide once weekly (EXQW) on HOMA-β. This meta assessed the comparative effects of EXQW and EXBID on HOMA-β among T2DM patients. Materials and Methods. PubMed, Cochrane Library, and Embase databases were searched to collect randomized controlled trials (RCTs). Network meta-analysis was performed, and network diagrams were constructed to evaluate the effects. The primary outcome is HOMA-β, and the secondary outcomes are fasting blood glycose (FBG), glycated hemoglobin (HbA1c), and weight loss. Results. A total of 8 studies with 3506 subjects were included. Compared with other antidiabetic agents, EXQW has a greater improvement in HOMA-β than EXBID (weight mean difference WMD=‐0.46, 95% confidence interval (CI) [-0.64, -0.28], P=0.001). The effect of EXQW on HbA1c is superior to that of sitagliptin (SITA) (WMD=0.51, 95% CI [0.03, 0.99], P=0.037). The significant reduction of weight was detected for EXBID in comparison with EXQW (WMD=‐0.73, 95% CI [-1.13, -0.33], P=0.001), and no significant difference was found between EXQW and MET. Conclusions. EXQW shows a greater improvement in HOMA-β than EXBID. Moreover, the efficacy of EXQW on glycemic control is similar to other antidiabetic agents including EXBID. It is an advisable treatment for diabetic patients to improve HOMA-β and has an advantage of fewer number of injections compared with EXBID, to increase patients’ adherence and quality of life.